The Impact Of Lavender Aromatherapy Techniques And Endorphin Massage On Anxiety During The First Active Phase - Febriantini, Asri; Mamlukah, Mamlukah; Wahyuniar, Lely; Nastiti Iswarawanti, Dwi (Jurnal Medisci, 2024)
Stress and an overabundance of catecholamine hormones released during labor can cause smooth muscle and uterine ischemia, which heightens pain impulses. A light touch or therapeutic massage stimulating the body to release endorphin compounds can relieve pain and comfort. This type of massage is known as endorphin massage. Linalool, a compound found in lavender aromatherapy, has calming and muscle-relaxing properties. This research project aims to ascertain "The Effectiveness of Lavender Aromatherapy and Endorphin Massage on Anxiety of Labor Pain in the First Active Phase in the Working Area UPTD Puskesmas Sukahaji." This study used a quasi-experimental design with pre-and post-test methods and a control group design carried out in the working area of UPTD Puskesmas Sukahaji. Purposive sampling was used to obtain samples. Purposive sampling was used to collect samples from 120 individuals. The Wilcoxon and Kruskal Wallis tests were used in the data analysis. The Wilcoxon test in bivariate analysis produced a p-value of less than 0.005 for every intervention group. The endorphin massage group's mean rank for the anxiety variable was 57.08; the control group's was 45.17; the lavender aromatherapy group's was 72.53; and the combination group's was 67.22. In conclusion, the anxiety associated with labor pain was impacted by endorphin massage, lavender aromatherapy, and the combination of the two. The best treatment for lowering anxiety was lavender aromatherapy, and the best way to lessen the severity of labor pain was to combine lavender aromatherapy with endorphin massage. Recommendation: It is believed that aromatherapy with lavender and endorphin massage can be used as alternative ways to reduce anxiety and the intensity of labor pain.